Physiological and locomotor demands during small-sided games are related to match demands and physical fitness? A study conducted on youth soccer players - Filipe Manuel Clemente; Ana Filipa Silva; Adam Kawczyński; Mehmet Yıldız; Yung-Sheng Chen; Sabri Birlik; Hadi Nobari; Zeki Akyildiz (BMC, 2022)
Abstract Aim The purpose of the study was: (i) to analyze the relationships of physiological and locomotor demands between small-sided games (3v3 and 5v5) and official matches (11v11); (ii) to analyze the relationships between small-sided games demands and the physical fitness of youth soccer players. Methods The observational study lasted three weeks. In the first week participants performed the 5v5 (50 × 31 and 40 × 25 m) repeatedly over four days. In the third week they repeatedly performed the 3v3 (39 × 24 and 32 × 19 m) over four consecutive days. Twenty youth soccer players (age: 16.8 ± 0.41) were tested twice for their final velocity at 30-15 Intermittent Fitness test (VIFT), peak speed attained at 30-m sprint test (peak speed), and anaerobic speed reserve (ASR). The heart rate responses and locomotor demands were monitored in the SSGs (3v3 and 5v5) and matches (11v11) occurring once a week. The Polar Team Pro was used as the instrument to monitor heart rate and locomotor demands. Three official matches were also monitored during the period. Results Results revealed no significant correlations (p > 0.05) between small-sided games and match physiological or locomotor demands. However, VIFT and ASR were significantly correlated with distance covered at 5v5 (r = 0.483; p = 0.031; and r = − 0.474; p = 0.035, respectively), average speed (r = 0.474; p = 0.035; and r = − 0.453; p = 0.045, respectively), while VIFT was also significantly correlated with distance covered at Z2 intensity (r = 0.510; p = 0.022). Conclusions The results suggest that the physiological and locomotor demands occurring in small-sided games are significantly different from those occurring in official matches. Thus, physiological and locomotor similarities between small-sided games and official matches are scarce. Considering the second purpose of this study, the results suggest that VIFT and ASR are important physical fitness parameters to modulate the amount of distance covered by the players in 5v5, the average pace, and also the distance covered at high intensities.